Organelle Optogenetics: Direct Manipulation of Intracellular Ca2+ Dynamics by Light - Asano, Toshifumi; Igarashi, Hiroyuki; Ishizuka, Toru; Yawo, Hiromu (Frontiers in Neuroscience, 2018)
As one of the ubiquitous second messengers, the intracellular Ca2+, has been revealed to be a pivotal regulator of various cellular functions. Two major sources are involved in the initiation of Ca2+-dependent signals: influx from the extracellular space and release from the intracellular Ca2+ stores such as the endoplasmic/sarcoplasmic reticulum (ER/SR). To manipulate the Ca2+ release from the stores under high spatiotemporal precision, we established a new method termed "organelle optogenetics". That is, one of the light-sensitive cation channels (channelrhodopsin-green receiver, ChRGR), which is Ca2+-permeable, was specifically targeted to the ER/SR. The expression specificity as well as the functional operation of the ER/SR-targeted ChRGR (ChRGRER) was evaluated using mouse skeletal myoblasts (C2C12): (1) the ChRGRER co-localized with the ER-marker KDEL; (2) no membrane current was generated by light under whole-cell clamp of cells expressing ChRGRER; (3) an increase of fluorometric Ca2+ was evoked by the optical stimulation (OS) in the cells expressing ChRGRER in a manner independent on the extracellular Ca2+ concentration ([Ca2+]o); (4) the deltaF/F0 was sensitive to the inhibitor of sarco/endoplasmic reticulum Ca2+-ATPase (SERCA) and (5) the store-operated Ca2+ entry (SOCE) was induced by the OS in the ChRGRER-expressing cells. Our organelle optogenetics effectively manipulated the ER/SR to release Ca2+ from intracellular stores. The use of organelle optogenetics would reveal the neuroscientific significance of intracellular Ca2+ dynamics under spatiotemporal precision.